O que o futuro nos reserva? Efeito das mudanças climáticas sobre a dinâmica populacional de pragas agrícolas no estado do Espírito Santo - Gomes, Fernanda de Freitas (2013)
The changes attributed to global warming are one of the biggest problems faced by current species on our planet, and temperature is afactor that influences the insects in their rates of growth, development and body size, thus directly or indirectly influencing their survival, reproduction and movement.As temperature increases, the development time decreases progressively. Based on this concept, a common approach for modeling the effects of temperature on development of insects is converting development time by using Degree-Days.Using average monthly temperaturesdata as independent variables, we can examine the variation in physiological attributes of living organisms by using mathematical models.Hosts and parasitoids have arefinedcoupling physiological relationship, in order that, if temperaturechanges, the efficiency of pest control by the parasitoid may be compromised.Studies evaluating the impact of temperature on the biology of Trichogrammacan help increase the establishment and effectiveness of these natural enemies in agricultural ecosystems.Thus, an expected increase in temperature in the state of the Espírito Santo, where agribusiness accounts for 80% of economic activity, can cause destabilization among the population dynamicsof insects that cause damage tocrops and species of parasitoid wasps that regulate them.The species Tutaabsoluta, Sitotroga cerealella, Trichogramma pretiosum e Trichogramma acacioiwere chosen to simulate how changes in climate affect the population dynamics of these insects to the present, 2020, 2050 and 2080.Using biological data of these species,were generated physiological timemodels, proving the physiological calibration between the system Host-Parasitoid;and population dynamics simulations projecting the present and future.In the case of Espírito Santo, is expected to occur an increase in temperature in 2080 ranged from 0,1 to 0,8°C comparing to present. T. absolutaand its parasitoid T. pretiosumhave a pattern amongtheir population densities in the present, but, for the future, the synchrony between the population densities islost.ToS.cerealella and T. acacioi, it is not possible to identify a pattern between hosts and parasitoidspopulations, since the population of S. cerealella is not influenced by temperature. The evidence of this study show that variations in temperature caused greater effect on populations of parasitoids than hosts